Dampak Modal Intelektual Terhadap Kinerja Keuangan Sektor Perbankan Dan Pertumbuhan Dana Pihak Ketiga Sebagai Moderasi - Ambo Sakka Hadmar; Andi Asnur Pranata M.H (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
The article explains about the effect of modal intelektual on financial performance and growth of third-party funds as a moderating variable. Modal intelektual is measured by the Value Added Modal intelektual (VAICTM) method, financial performance is measured by return on equity (ROE). The population of this research is banking companies listed on the IDX in 2016-2020. The technique used in determining the sample is purposive sampling with a total of 200 observations at banking companies. The analytical technique used in this research is Moderate Regression Analysis (MRA). The hypothesis is accepted if the probability value is 0.05. The results of this study indicate that: (1) modal intelektual has no effect on financial performance, (2) growth of third-party funds strengthens the influence of modal intelektual on financial performance, (3) growth of third party funds does not moderate the effect on financial performance.